PERAN HUMAN CAPITAL BAGI KEUNGGULAN KOMPETITIF ORGANISASI: SEBUAH TINJAUAN - Suryono Efendi (Globalwriting Academica Consulting & Publishing, 2019)
With rising globalization and labor market saturation, the present downturn in many international economies has emphasized the importance of human capital. Both developed and developing countries place a premium on human resource development in order to boost economic growth through increased time and effort. Human resource development is a critical component in entering the international arena. To do this, businesses must invest the required resources in developing human capital that has a stronger influence on performance. From a variety of critical viewpoints, the influence of this paper evaluation on human capital has a direct effect on company performance. The success of the business is measured in both financial and non-financial parameters. Finally, this article develops an early model of the connection between human capital and business performance.